METODE PENANAMAN NILAI SOSIAL PADA SANTRI DI PONDOK PESANTREN SALAFIYAH DAN IMPLEMENTASINYA DALAM KEGIATAN MASYARAKAT PULUTAN LOR RW 02 KECAMATAN SIDOREJO KOTA SALATIGA TAHUN 2018 - Jamasri Jamasri; Yosaphat Haris Nusarastriya (PKn Progresif : Jurnal Pemikiran dan Penelitian Kewarganegaraan, 2018)
This study is titled the method of planting social value in santri at the Salafiyah Islamic Boarding School RW 02, Sidorejo sub-district, Salatiga city in 2018. This type of research is a qualitative descriptive study with 45 research subjects as kyai and santri. Data was collected by observation, interviews, documentation, and questionnaires. Data analysis using qualitative descriptive techniques. The results showed that the method of planting social values used was the Sorogan and Bandongan methods. The embedded social values include discipline, empathy, respect, caring, and tolerance. The implementation of the social values of santri in community activities is to become a TPA worker, a large study committee and mutual cooperation. Keywords:  social values, santri, islamic boarding schools, community activities